2016
DOI: 10.3109/1547691x.2016.1143539
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 regulates apoptosis induced by asbestos in the MT-2 human T-cell line

Abstract: Asbestos is known to cause malignant mesothelioma and lung cancer. Recent studies implicate tumor immunity in the development of various tumors, including malignant mesothelioma. In order to establish an in vitro T-cell model to clarify the effects of long-term exposure of asbestos on tumor immunity, in this study, human T-cell line MT-2 cells were cultured with asbestos for longer than 8 months and the resultant cells (MT-2Rst) were assessed for the expression of forkhead transcription factor FoxO1. Gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…These sublines showed resistance against the asbestos-induced apoptosis via upregulation of IL-10, increased phosphorylation of STAT3 by autocrine usage of IL-10, and subsequent upregulation of Bcl-2 located downstream of STAT3 (22). Moreover, our recent study revealed that reduced FoxO1 caused reduction of other apoptosis-related molecules such as Bim, Puma, and Fas ligand, which are known to be regulated by FoxO1 (31). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These sublines showed resistance against the asbestos-induced apoptosis via upregulation of IL-10, increased phosphorylation of STAT3 by autocrine usage of IL-10, and subsequent upregulation of Bcl-2 located downstream of STAT3 (22). Moreover, our recent study revealed that reduced FoxO1 caused reduction of other apoptosis-related molecules such as Bim, Puma, and Fas ligand, which are known to be regulated by FoxO1 (31). …”
Section: Discussionmentioning
confidence: 99%
“…The procedures for western blotting were performed according to the previously reported methods (31). Briefly, MT-2Org cells and cells from asbestos continuously exposed sublines were lysed in 20 mM Tris-HCl (pH 7.5) containing 1 mM EDTA, 1 mM EGTA, 10 mM 2-mercaptoethanol, 1% Triton X-100, 1% sodium deoxycholate, 0.1% sodium lauryl sulfate, 150 mM NaCl and 1% protease inhibitor cocktail (Sigma) and briefly sonicated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations